Strategi positioning toko madura sebagai market challenger untuk keunggulan kompetitif ditinjau dari risiko dan etika - Sugeng Eko Yuli Waluyo; Ahfi Nova Ashriana; Rachmad Sholeh (Universitas Negeri Surabaya, 2026)
This study analyzes the positioning strategy used by Madura stores to attract consumers to shop there. The positioning strategy employed is that Madura stores are open 24 hours a day and offer lower prices than modern retailers. This qualitative study employed a Systematic Literature Review, a structured research method used to collect, analyze, and identify other research evidence relevant to the author's topic. The results of this study indicate that by choosing a 24-hour positioning, Madura stores can compete with modern retailers such as Indomaret and Alfamart in attracting customers. However, this also increases safety and security risks. In terms of business ethics and risk management, special attention is also needed when a retail store business is only run by a husband and wife working 24 hours non-stop, without an employee recruitment system, shift schedule, wage system, modern bookkeeping, technological support such as CCTV, computerization, networks with several digital payment merchants and ATM machines.